EFFICIENCY ANALYSIS OF FREE ZONES AND STRATEGY POLICIES - (:unkn) unknown (FUTURE ACAD, 2019)
Free Zones are defined as areas that are partially or totally exempt from legal and administrative regulations relating to many aspects such as commercial, financial and economic areas existing in the country. These areas are set up to promote industrial and commercial activities, export-oriented investment and production, accelerating foreign direct investment and technology transfer, directing exports to businesses and developing international trade (Ministry of Economy, Republic of Turkey). Sustaining the efficiency of Free Zones is crucial since they steer both regional and macro economies in the country. If a Free Zone is not able to provide the employees of its member firms with financial well-being and begin to rely on governmental bodies to operate, then it is very likely for that Free Zone to be a burden on the economy and become inefficient in terms of output/input ratio. In this study, a data envelopment analysis is applied to measure the efficiencies of 18 Free Zones in Turkey within the scope of a project conducted in partnership with the Eastern Black Sea Regional Development Administration (DOKAP) and policies are suggested as reflected by the sensitivity analyses of their respective mathematical models. 9 out of 18 Free Zones have been found inefficient, 3 of them showed a rate smaller than 20%. It is seen that most of the Free Zones are not at desired exportation levels. Moreover, some of them having the efficiency ratio closer to 1 actually do not have satisfactory export levels. (C) 2019 Published by Future Academy www. FutureAcademy. org. UK
Keywords: Free zones; data envelopment analysis; strategic management; foreign trade; UNEMPLOYMENT